2020
DOI: 10.22487/j24428744..v.i.15051
|View full text |Cite
|
Sign up to set email alerts
|

Pemberian Informasi Obat Pasien Dengan Resep Antibiotik dan Penyediaan Antibiotik Tanpa Resep di Tangerang Selatan

Abstract: A pharmacy is a place where pharmacists do their pharmaceutical work, serving directly and responsibly for patients who need their professional services. One form of direct service is the provision of drug information and counseling. The purpose of this study was to describe the drug information services provided by pharmaceutical personnel in the South Tangerang area pharmacy for patients who redeemed prescriptions using antibiotics. Patient simulation method was used to collect data to 100 pharmacies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Selaras pada pengkajian yang diselenggarakan Hend Wageh Abozed mengatakan bila "pengetahuan yang kurang terdeteksi pada ibu dengan tingkat pendidikan rendah" (15). Interaksi obat dengan obat lainnya perlu dipertimbangkan, dan efek samping obat perlu dijelaskan kepada pasien (17). Biljana Mijović, dkk.…”
Section: Pembahasanunclassified
“…Selaras pada pengkajian yang diselenggarakan Hend Wageh Abozed mengatakan bila "pengetahuan yang kurang terdeteksi pada ibu dengan tingkat pendidikan rendah" (15). Interaksi obat dengan obat lainnya perlu dipertimbangkan, dan efek samping obat perlu dijelaskan kepada pasien (17). Biljana Mijović, dkk.…”
Section: Pembahasanunclassified
“…All seven studies included in the review on dispensing antibiotics without a prescription from Indonesian community pharmacies used a simulated patient study design. Two studies were reported from Surabaya (Hadi et al, 2010;Puspitasari et al, 2011), one study from Tangerang (Listyorini et al, 2021), South Tangerang (Saibi et al, 2020), and eastern Indonesian provincial capital (Brata et al, 2019). Moreover, one study was conducted in four districts in Palembang (Simamora et al, 2020), and one study was conducted in urban and rural areas, namely Bekasi City and Tabalong District (Wulandari et al, 2021).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The purpose of these studies was to investigate the actions taken by community pharmacists on requests for antibiotics without prescriptions. In addition, several studies have sought to assess pharmacists' provision of drug information services for dispensing antibiotics without a prescription (Listyorini et al, 2021;Puspitasari et al, 2011;Saibi et al, 2020).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Currently, pharmacists are required to always improve their knowledge, skills, and professionalism to carry out direct interactions with patients (Permenkes RI 2016). Drug Information Services (PIO) is part of clinical pharmacy services, which is also the duty and responsibility of a pharmacist and is a very important part to be able to improve the quality of public health (Saibi et al 2020). The paradigm shift from drug-oriented to patient-oriented with the pharmaceutical care paradigm is the result of demands from consumers.…”
Section: Introductionmentioning
confidence: 99%